Aesthetics and Simbolism: The Essence of Purple Colour in Yuni Film (Cinematology: Journal Anthology of Film and Television Studies, 2024)
Aesthetics in multimedia works is defined as an artistic phenomenon to beautify the form of moving image works. Aesthetics plays a role in the elements of film visualization and creates symbols that can be identified by the audience. Aesthetics and symbolism in film function as a communication and foundation for understanding accompanied by creative ideas. The meaning of aesthetics cannot be separated from the form of meaning of an object related to an idea and feeling. One of the Indonesian films that applies aesthetics through artistic elements is Yuni film. The film tells of a student named Yuni who is frustrated between continuing her education to college or getting married at an early age because of the patriarchal culture inherent in her social environment. Yuni's character is synonymous with the color purple based on three elements, namely clothing, setting, and object/property because it has its own meaning for the theme of the story and the character's character. This study uses a qualitative method with an analytic descriptive approach. Sources of data come from Yuni film and scientific journals that examine similar topics regarding the film's work. The data analysis technique was carried out by watching Yuni film and interpreting the meaning of the purple color present in it. The result of this study is that the color purple is a symbol for the identity/characteristics of the Yuni character and has its own artistic value in it.